2021
DOI: 10.1038/s41420-021-00619-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mature dendritic cells homing to the thymus promote thymic epithelial cells involution via the Jagged1/Notch3 axis

Abstract: Multiple proinflammatory conditions, including chemotherapy, radiotherapy, transplant rejection, and microbial infections, have been identified to induce involution of the thymus. However, the underlying cellular and molecular mechanisms of these inflammatory conditions inducing apoptosis of thymic epithelial cells (TECs), the main components of the thymus, remain largely unknown. In the circulation, mature dendritic cells (mDCs), the predominant initiator of innate and adaptive immune response, can migrate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Since S1 contains the receptor binding domain of the spike protein, it could bind to the ACE2 receptors on mTECs, inducing a damaging inflammatory effect, as has been demonstrated for endothelial cells [69]. Even independently of the spike protein, returning DCs have been shown to directly inhibit TEC proliferation and induce their apoptosis by activating the Jagged1/Notch3 signalling pathway [95].…”
Section: Potential For Damage To the Thymic Epithelium And Accelerate...mentioning
confidence: 96%
“…Since S1 contains the receptor binding domain of the spike protein, it could bind to the ACE2 receptors on mTECs, inducing a damaging inflammatory effect, as has been demonstrated for endothelial cells [69]. Even independently of the spike protein, returning DCs have been shown to directly inhibit TEC proliferation and induce their apoptosis by activating the Jagged1/Notch3 signalling pathway [95].…”
Section: Potential For Damage To the Thymic Epithelium And Accelerate...mentioning
confidence: 96%
“…APCs, like dendritic cells (DCs), are efficient immune forerunners. [ 114,115 ] Apart from limiting T cell proliferation, the immunosuppressive tumor milieu reduces DC migration, stimulation, and antigen presentation. [ 44,111 ] Researchers have been striving to develop artificial APCs (aAPCs) as a substitute for innate APCs for the past 20 years.…”
Section: Nanoparticles/drug Hitchhiking Tactics On Immune Cells For C...mentioning
confidence: 99%
“…Since a majority of thymic DCs come from the periphery, whether migratory DCs play a role in thymus damage post infection was unclear. A recent publication by Haojie Wu et al showed that mature DCs from the circulation can enter the thymus and induce thymus involution through the Notch signaling pathway (47). Upon activation by antigens such as lipopolysaccharide and ovalbumin, DCs have been shown to enhance Jagged1 expression (48,49).…”
Section: Thymic Dendritic Cells In Post Infectionmentioning
confidence: 99%